Islamic Spiritual-based Health Promotion on the Basic Immunization and the Knowledge and Attitudes of the Mothers - Simanjuntak, Samuel M.; Nurnisa, Indah (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
It was found that only 25 % of mothers with a toddler understood the importance of basic immunization and the basic immunization schedule in their area. The purpose of this study was to determine the influence of the Islamic spiritual-based health promotion of toddlers’ basic immunization on the mothers’ knowledge and attitudes about the immunization at RW.06 Sukajaya village. The method used in this study was quasi-experimental with one group pretest post-test without control. The data gathered in this study were obtained from questionnaires filled by the respondents and analyzed by using SPSS. The results of data analysis showed that there were significant differences regarding the mothers’ knowledge about toddlers basic immunization before and after the Islamic spiritual-based health promotion of the immunization at RW.06 Sukajaya village with p-value <0.05, and there were significant differences towards the mothers’ attitudes regarding the toddlers’ basic immunization before and after the health promotion of the immunization at RW.06 Sukajaya village with p-value = 0.00. This study concludes that the faith-based counsel given to the mothers regarding the toddlers’ basic immunization had significantly increased the mothers’ knowledge and attitudes. From the results of this study, it is suggested for the nurses or related health professional workers to give more attention to the need of conducting faith-based health promotions on basic immunization on a regular basis to the public, especially mothers with toddlers in order to improve the health standard of Indonesian children. Keywords : Attitude, Basic immunization, Islamic spiritual-based health promotion, Knowledge